Diversion and Juvenile Narcotics Sentencing: Indonesia and Japan Comparison under Pancasila Justice - Mulyadi Alrianto Tajuddin; Jumriani Nawawi; Jaco Barkhuizen (Fakultas Hukum Universitas Muhammadiyah Sorong, 2026)
This study aims to analyze the policy of diversion and criminalization of children in narcotics cases in the juvenile criminal justice system in Indonesia, and compare it with practices in Japan to identify systemic problems that hinder rehabilitative orientation. This study uses normative legal methods with legislative, conceptual, and comparative approaches. The analysis focused on the provisions in Law No. 11 of 2012 concerning the Juvenile Criminal Justice System and Law No. 35 of 2009 concerning Narcotics, as well as their comparison with the welfare-oriented juvenile justice system in Japan. The novelty of this research lies in the placement of Pancasila justice as an evaluative framework in analyzing the design of the juvenile criminal justice system, so that diversion is not understood solely as a procedural mechanism, but as a systemic principle that must integrate rehabilitation and social reintegration. The findings of the study show that the failure to implement diversion in narcotics cases against children is more due to normative restrictions and fragmentation of goals between criminal justice subsystems, rather than solely by technical implementation issues. This study concludes that policy reconstruction is needed by placing rehabilitation as the main response and imprisonment as the ultimate remedium, in order to realize child protection that is in line with human values and social justice within the framework of Pancasila justice.